CLASSICAL HERITAGE AND EUROPEAN IDENTITIES - Funder, Lærke Maria Andersen. ([Place of publication not identified])
1 online resource.
Keywords: Classical Heritage and European Identities examines how the heritages of classical antiquity have been used to construct European identities, and especially the concept of citizenship, in Denmark from the eighteenth century to the present day. It implements a critical historiographical perspective in line with recent work on the "reception" of classical antiquity that has stressed the dialectic relationship between past, present and future. Arguing that the continuous employment and appropriation of lassical heritages in the Danish context constitutes an interesting case of an imagined geography that is simultaneously based on both national and European identities, the book shows how Denmark's imagined geography is naturalized through very distinctive uses of classical heritages within the educational and heritage sectors. It does so by exploring three significant and interrelated arenas where the heritages of classical antiquity are used to shape Danes as European citizens. Together, these three cases emphasize different but interconnected ways in which classical heritages are being put to use in order to construct Denmark's own distinctive national identity within Europe. Finally, the book also sheds light on some of the challenges that face unified and homogenous conceptions of European heritage and identity, as well as the notion of the "classical" itself. Classical Heritage and European Identities is the first English-language monograph to situate the Danish case within the wider European context. As such, the book should be essential reading for researchers and students engaged in the study of heritage and museums, classics, education and modern European history.